Iranian Diaspora, Reality Television and Connecting to Homeland - Elham Atashi (Media and Communication, 2018)
Befarmaeed Sham, an Iranian diasporic media production adapted from the original UK reality show “Come Dine with me” features Iranian diaspora of diverse backgrounds as contestants in a cooking reality show. The success of the show has been unprecedented among audiences back home in Iran, reaching millions of households. Using discourse analysis this article examines the potential of reality TV in widening the scope of public sphere and in providing a space for participation and representation. The key practices to illustrate this are ways diaspora position themselves as subjects through discursive practices to express agency in generating, participating and sharing opinions. Casual talk and the entertaining attribute of reality TV focused on the everyday life of ordinary people, constructs a space to normalize audience engagement with what is otherwise, restrictive taboo topics embedded in themes around belonging, homeland, gender, and identity. The article concludes that the broad system of discourse used by diaspora as participants in the reality show constructs a space for representation. It can be considered as a contribution to enhancing the public sphere to not only communicate and connect with their homeland but to express opinions on broader social issues as a practice of civic engagement. This unique adaptation of reality TV is an important aspect of globalization and in using new media to mobilize diaspora in connecting to homeland.